2007
DOI: 10.1677/erc-06-0045
|View full text |Cite
|
Sign up to set email alerts
|

Critical assessment of new risk factors for breast cancer: considerations for development of an improved risk prediction model

Abstract: The majority of candidates for breast cancer prevention have not accepted tamoxifen because of the perception of an unfavorable risk/benefit ratio and the acceptance of raloxifene remains to be determined. One means of improving this ratio is to identify women at very high risk of breast cancer. Family history, age, atypia in a benign biopsy, and reproductive factors are the main parameters currently used to determine risk. The most powerful risk factor, mammographic density, is not presently employed routinel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
129
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 176 publications
(134 citation statements)
references
References 88 publications
(64 reference statements)
1
129
0
4
Order By: Relevance
“…This mechanism of estrogen production can lead to local estrogen levels in breast tumors that are as much as 10-fold higher compared with the circulation. In fact, a recent publication assessing breast cancer risk factors listed BMI and weight gain between the ages of 20 and 50 years as second only to Gail Model parameters [quantitative breast density, free estradiol, parity (yes/no), and age of menopause] in importance (79). The association between obesity and breast cancer risk is complex, varying by breast cancer subtype and by menopausal status.…”
Section: Cancermentioning
confidence: 99%
“…This mechanism of estrogen production can lead to local estrogen levels in breast tumors that are as much as 10-fold higher compared with the circulation. In fact, a recent publication assessing breast cancer risk factors listed BMI and weight gain between the ages of 20 and 50 years as second only to Gail Model parameters [quantitative breast density, free estradiol, parity (yes/no), and age of menopause] in importance (79). The association between obesity and breast cancer risk is complex, varying by breast cancer subtype and by menopausal status.…”
Section: Cancermentioning
confidence: 99%
“…This conclusion is based on the observations that several oestrogen-related events such as early menarche, age at menopause, plasma oestrogen levels, BMI, and menopausal hormone therapy (MHT) are all associated with an increased risk of breast cancer ( Fig. 8; Santen et al 2007). Two large multi-center studies demonstrated a linear relationship between breast cancer risk and increasing oestradiol ( Fig.…”
Section: Mechanisms Of Oestrogen Associated Carcinogenesismentioning
confidence: 99%
“…The difference in risk between women with extremely dense, as opposed to predominantly fatty breasts is approximately 4-to 6-fold (15). Incorporation of density into the standard risk prediction models is associated with some improvement in risk prediction (16,17).…”
Section: Introductionmentioning
confidence: 99%